Characterization and genomic analysis of Salmonella Abortusequi phage, vB_SalP_LDDK01, and its biocontrol application in donkey meat - Cao, Shengliang; Kong, Xinyu; Liu, Yixuan; Wang, Zhiwei; Zhang, Zhi; Lei, Xiaojing; Li, Pan; Wang, Liting; Yang, Fan; Liu, Shiyang; Li, Rongyue; Li, Yubao; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Salmonella Abortusequi (S. Abortusequi) is the primary cause of abortions in equine animals, and can cause serious foodborne illness. Thus, effective biocontrol strategies are needed to decontaminate and control the emergence of foodborne diseases. In recent years, phages have been used as a new strategy for modulating foodborne pathogens and food safety. In this study, a new phage, vB_SalP_LDDK01, was isolated from donkey farm bedding. The data indicated that the incubation period of vB_SalP_LDDK01 was 10 min, the burst size was 378 PFU/cell, as well as a wide range of heat resistance (40-70°C) and pH stability (4-12). Furthermore, genomic analysis and electron microscopy indicated that vB_SalP_LDDK01 belongs to the Class Caudoviricetes and genus Jerseyvirus. Moreover, its genome was 42,378 bp long, encoded 57 ORFs, was double-stranded DNA with a 49.52% GC content, and lacked virulence and drug-resistant genes. In addition, how vB_SalP_LDDK01 inhibits the growth of S. Abortusequi and removes the biofilm of S. Abortusequi was assessed in a liquid broth medium, and the results showed that vB_SalP_LDDK01 inhibited the growth of S. Abortusequi for about 8 h and significantly reduced the viable bacteria abundance compared with the phage-free positive control. Further, vB_SalP_LDDK01 treated the host bacteria for 12 h and effectively destroyed the biofilm of S. Abortusequi. This study further investigated how effectively vB_SalP_LDDK01 modulates bacterial contamination in donkey meat inoculated with S. Abortusequi LCU-S-ABORT-F at 4°C and 25°C. Furthermore, after 72 h of vB_SalP_LDDK01 treatment with different multiplicity of infection (1, 0.1, 0.01, and 0.001), the bacterial contamination on the surface of donkey meat was reduced by 4.3, 3.7, 3.3, and 3.5 log10 CFU/piece at 25°C, and 4.5, 3.9, 2.8, and 2.7 log10 CFU/piece at 4°C. Whereas the phage titers at different temperatures were basically comparable to the initial titers. Overall, these results indicated that vB_SalP_LDDK01, the new phage, can serve as an effective biological agent and inhibit S. Abortusequi in donkey meat.